Moderating role of managerial ambidexterity in the relationship between intellectual capital and financial performance. - Ortiz-Regalado, O. (2025)
Type of the article: Research Article AbstractIntangible assets represent a crucial source of competitive advantage, particularly for small and medium-sized enterprises in emerging markets. This study examines the moderating role of managerial ambidexterity in the relationship between intellectual capital and financial performance. A quantitative, non-experimental, cross-sectional design was employed, and data were collected from 530 manufacturing firm workers between March and August 2024. The measurement models were validated through assessments of convergent and discriminant validity, while the hypothesized relationships were tested using structural equation modeling with SPSS 27 and AMOS 28. The empirical results demonstrate that intellectual capital exerts a significant positive effect on financial performance (β = 0.257, p < .001). Moreover, managerial ambidexterity significantly moderates this association, further strengthening the intellectual capital–financial performance relationship (interaction β = 0.081, p < .001). In addition, the structural model exhibited satisfactory fit indices, confirming the robustness of the analysis. The study concludes that intellectual capital constitutes a key strategic resource for enhancing financial performance, and its impact is substantially amplified when firms develop managerial ambidexterity capabilities that enable a balance between efficiency and innovation. Finally, this study adds value by demonstrating how intellectual capital and managerial ambidexterity jointly enhance financial performance. Moreover, it addresses a critical research gap in emerging markets, where empirical evidence remains scarce. The findings extend the resource-based view by confirming the synergistic role of dynamic capabilities in emerging-market SMEs.